A novel g-C3N4/BiOI/Ag2WO4 heterojunction for efficient degradation of organic pollutants under visible light irradiation. Issue 18 (15th September 2021) - Liao, Ya; Zou, Changjun; Peng, Hong; Lin, Shuai; Chen, Wenjing; Cao, Yixuan; Li, Bingqian
Abstract: In recent years, photocatalytic technology has attracted wide attention in the treatment of dye wastewater due to its green and efficient performance. In this study, a novel heterojunction of g-C3 N4 /BiOI/Ag2 WO4 was synthesized and the photocatalytic activity was evaluated through degrading Sudan red III. The results of XRD, FT-IR, SEM, TEM and XPS revealed that BiOI and Ag2 WO4 were successfully loaded onto the surface of g-C3 N4 . According to the results of UV–vis DRS and PL spectra, the g-C3 N4 /BiOI/Ag2 WO4 exhibited excellent photocatalytic activity. Moreover, the g-C3 N4 /BiOI/Ag2 WO4 showed an excellent efficiency for the degradation of Sudan red Ⅲ and the degradation rate up to 89% in 90 min. The novel photocatalyst significantly shortened the degradation time, and improved the degradation rate. This study provided a theoretical basis for efficient degradation of Sudan red Ⅲ.